MODELING OF MICRO HYDROPOWER PLANTS OPERATING UNDER LOW PRESSURE AND HIGH-WATER FLOW - Uzbekov Mirsoli Odiljonovich; Sanjarbek Rakhmonjonovich Ormonov (European Science Publishing, 2024)
Micro hydropower plants (MHPs) are a promising solution for harnessing renewable energy, particularly in regions with high water flow but low-pressure environments, such as streams and small rivers. This paper presents a comprehensive model for the operation of MHPs under low pressure and high flow rate conditions, emphasizing their efficiency, energy output, and feasibility in remote or rural areas. The model incorporates key hydrodynamic parameters and turbine performance metrics to optimize power generation. Through computational simulations and real-world data analysis, the study demonstrates that MHPs can be an effective and sustainable energy solution. The findings highlight the potential of these systems to contribute significantly to the global transition towards greener energy, with minimal environmental disruption. This research provides a framework for further development and deployment of MHPs, particularly in geographically challenging areas.
Keywords: Micro hydropower plants (mhps), low pressure hydropower, high water flow energy, renewable energy, small-scale hydropower, water turbine optimization, low-head hydropower, sustainable energy systems, rural energy solutions.